Review of Single Bubble Motion Characteristics Rising in Viscoelastic Liquids - Wei Wang (International Journal of Chemical Engineering, 2021)
The emphasis of this review is to discuss three peculiar phenomena of bubbles rising in viscoelastic fluids, namely, the formation of a cusp, negative wake, and velocity jump discontinuity, and to highlight the possible future directions of the subject. The mechanism and influencing factors of these three peculiar phenomena have been discussed in detail in this review. The evolution of the bubble shape is mainly related to the viscoelasticity of the fluid. However, the mechanisms of the two-dimensional cusp, tip-streaming, “blade-edge” tip, “fish-bone” tip, and the phenomenon of the tail breaking into two different threads, in some special viscoelastic fluids, are not understood clearly. The origin of the negative wake behind the bubbles rising in a viscoelastic fluid can be attributed to the synergistic effect of the liquid-phase viscoelasticity, and the bubbles are large enough; thus, leading to a very long relaxation time taken by the viscoelastic stresses. For the phenomenon of bubble velocity jump discontinuity, viscoelasticity is the most critical factor, and the cusp of the bubbles and the surface modifications play only ancillary roles. It has also been observed that a negative wake does not cause velocity jump discontinuity.